1987
DOI: 10.1152/ajprenal.1987.252.6.f1028
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic calcium and the action of vasopressin in toad urinary bladder

Abstract: The effects of experimental procedures believed to increase cytosolic calcium on basal and vasopressin-stimulated osmotic water flow and transepithelial sodium transport were examined in the toad urinary bladder. Exposure of isolated toad bladders to quinidine, calcium ionophores (A23187, X537A), or low-sodium or potassium-free serosal solutions resulted in a dose-dependent decrease in the hydrosmotic response to vasopressin or exogenous adenosine 3',5'-cyclic monophosphate (cAMP). The degree of inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Since, however, the amiloridesensitive component of the short-circuit cur rent was diminished, only Na absorption seems to be affected under these conditions. Such inhibition of Na transport, found also in other Na transporting epithclia, might be caused by enhanced cellular Ca and/or H con centrations due to inhibition of Ca/Na and H/ Na antiporters [10,11],…”
Section: Transepithelial Electrical Parametersmentioning
confidence: 90%
“…Since, however, the amiloridesensitive component of the short-circuit cur rent was diminished, only Na absorption seems to be affected under these conditions. Such inhibition of Na transport, found also in other Na transporting epithclia, might be caused by enhanced cellular Ca and/or H con centrations due to inhibition of Ca/Na and H/ Na antiporters [10,11],…”
Section: Transepithelial Electrical Parametersmentioning
confidence: 90%
“…Ca 2+ as an important second messenger, has been implicated to inhibit ENaCs (Wang and Chan, 2000). In particular, increase in cytoplasmic Ca 2+ results in decrease of apical Na + permeability in the frog skin (Grinstein and Erlij, 1978), toad urinary bladder (Brem et al, 1985;Palmer, 1985;Taylor et al, 1987) and the rabbit cortical collecting tubule (Frindt et al, 1993;Frindt and Windhager, 1990;Windhager et al, 1986). However, it is still unclear whether this inhibition is due to a direct effect.…”
Section: Namentioning
confidence: 99%
“…basolateral cell membrane and activates adenylate cyclase, resulting in the generation of cyclic AMP which serves as an intracellular messenger for both the hydrosmotic and natriferic action of the hormone. The mechanism of the events that follow cyclic AMP generation is not clear but cytoskeletal organelles, such as microtubules and actin-containing microfilaments, are thought to be involved in producing specific changes in the surface architecture (Taylor et al, 1987). We have confirmed that toad hemibladder tissue is highly sensitive to the hydrosmotic effect of AVP and that the preparation can be used to relate the antidiuretic activity of other pharmacological agents to AVP.…”
Section: Effect Of Arginine Vasopressinmentioning
confidence: 52%